2005
DOI: 10.1097/01.mlr.0000159975.43573.8d
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Research on Racial and Ethnic Disparities in Health Care Over Place and Time

Abstract: B lack Americans have substantially higher rates of cardiovascular mortality than other racial and ethnic groups in the United States, and they have experienced much less improvement in this important outcome than white Americans over the past 15 years. 1,2 Racial disparities in cardiovascular treatment contributing to this mortality gap have been extensively documented. [3][4][5] Numerous deficiencies, however, limit the usefulness of prior studies of racial and ethnic disparities in health care to guide poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…34 We found that most of the disparities in HEDIS outcome measures were attributable to different outcomes for black and white individuals enrolled within the same health plan. Moreover, the proportion of black enrollees within a plan was not an independent predictor of clinical performance.…”
Section: Quality Of Care and Racial Disparities In Medicarementioning
confidence: 77%
“…34 We found that most of the disparities in HEDIS outcome measures were attributable to different outcomes for black and white individuals enrolled within the same health plan. Moreover, the proportion of black enrollees within a plan was not an independent predictor of clinical performance.…”
Section: Quality Of Care and Racial Disparities In Medicarementioning
confidence: 77%
“…27,28 Within-Facility Versus Between-Facility Disparities To address racial disparities in the quality of care, it is critical to understand the relative contributions of within-facility disparities (differential results for black and white patients treated in the same facility) and betweenfacility disparities (concentration of black patients among facilities that perform poorly for all patients, irrespective of race). 29,30 These two sources of disparity demand different types of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis that distinguishes between these 2 explanations-disparities within hospitals and disparities that occur because blacks go to different hospitals than whites-is therefore critical for future research on disparities. 57 The potential benefits that come from increasing quality of care are well understood. 58 -61 One implication of the present study is that reducing mortality rates in high-mortality hospitals can have implications for reducing racial disparities in health outcomes.…”
Section: Discussionmentioning
confidence: 99%